MLH1 Promotor Hypermethylation in Colorectal and Endometrial Carcinomas from Patients with Lynch Syndrome - Helderman, Noah; Andini, Katarina; van Leerdam, Monique E.; van Hest, Liselotte P.; Hoekman, Daniël R.; Ahadova, Aysel; Bajwa-ten Broeke, Sanne W.; Bosse, Tjalling; van der Logt, Elise M. J.; Imhann, Floris; Kloor, Matthias; Langers, Alexandra M. J.; et al. (The journal of molecular diagnostics, 2024)
Screening for Lynch syndrome (LS) in colorectal cancer (CRC) and endometrial cancer patients generally involves immunohistochemical staining of the mismatch repair (MMR) proteins. In case of MLH1 protein loss, MLH1 promotor hypermethylation (MLH1-PM) testing is performed to indirectly distinguish the constitutional MLH1 variants from somatic epimutations. Recently, multiple studies have reported that MLH1-PM and pathogenic constitutional MMR variants are not mutually exclusive. This study describes 6 new and 86 previously reported MLH1-PM CRCs or endometrial cancers in LS patients. Of these, methylation of the MLH1 gene promotor C region was reported in 30 MLH1, 6 MSH2, 6 MSH6, and 3 PMS2 variant carriers at a median age at diagnosis of 48.5 years [interquartile range (IQR), 39-56.75 years], 39 years (IQR, 29-51 years), 58 years (IQR, 53.5-67 years), and 68 years (IQR, 65.6-68.5 years), respectively. For 31 MLH1-PM CRCs in LS patients from the literature, only the B region of the MLH1 gene promotor was tested, whereas for 13 cases in the literature the tested region was not specified. Collectively, these data indicate that a diagnosis of LS should not be excluded when MLH1-PM is detected. Clinicians should carefully consider whether follow-up genetic MMR gene testing should be offered, with age <60 to 70 years and/or a positive family history among other factors being suggestive for a potential constitutional MMR gene defect.